Prospective Analysis of Surgical Treatment For Displaced Midshaft Clavicle Fractures in Adults - Gurung, Sandeep; K.C., Dipendra (Journal of Nepalgunj Medical College, 2017)
Background: The traditional view that the vast majority of midshaft clavicular fractures heal with good functional outcomes following non-operative treatment may be no longer valid for all midshaft clavicular fractures. And it is becoming increasingly apparent that clavicular malunion is a distinct clinical entity with radiographic, orthopedic, neurologic, and cosmetic features. Recent studies have shown a high prevalence of symptomatic malunion and nonunion after nonoperative treatment of displaced midshaft clavicular fractures. Objective: To analyze the demography of midshaft clavicular fracture and to observe union time, DASH score, and complication of surgical treatment. Materials and Methods: This prospective observational study of 34 cases with midshaft clavicle fracture was conducted in Nepalgunj medical college, Kohalpur in a time span of one year. Patients were treated operatively with plating and followed up at 6 weeks, 12 weeks, 18 weeks, 6 and 12 month. Results: Thirty four patients (Male: 29 Female: 5) with average age 32.95 years (range: 19 to 59 years) were operated for clavicular fracture with male predominance (85.30%). The mean time for fracture healing was 16.24 weeks and mean DASH score was 13.58. Conclusions: Displaced midshaft clavicular fracture can be effectively managed with plating and have improved functional outcome and shorter time for union. JNGMC Vol. 13 No. 2 December 2015, Page: 17-20